DETERMINANTS OF FINANCIAL INCLUSION IN MSMEs: THE ROLE OF TECHNOLOGY, LITERACY, AND FINANCIAL VULNERABILITY - Siti Zulaekha; Zulfikar (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of electronic payment usage, fintech adoption, financial innovation, financial literacy, and financial vulnerability on financial inclusion among Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative approach, primary data were collected from 100 MSMEs through purposive sampling and analyzed with Multiple Linear Regression (SPSS 27). The results show that all variables simultaneously influence financial inclusion (R² = 75.1%). Partially, fintech adoption, financial innovation, financial literacy, and financial vulnerability have positive and significant effects. However, electronic payment usage shows a negative coefficient, indicating potential limitations in its effectiveness in promoting broader financial inclusion.